ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN ANTENATAL CARE DAN PEMILIHAN PERSALINAN DI PUSKESMAS LHOKSUKON KABUPATEN ACEH UTARA TAHUN 2020 - Husna Maulida (Getsempena Health Science Journal, 2022)
A B S T R A C T Maternal Mortality Rate (MMR) is one of the development targets and one of the sensitive indicators in describing the welfare of the community in a country. In this case the effort to reduce the MMR is very much in need of quality Ante Natal Care (ANC) and Intranatal Care (INC) services, The purpose of this study was to analyze the factors associated with the implementation of Antenatal care and the selection of labor Lhoksukon Community Health Center Working Area North Aceh District in 2020. The type of this research is observational analytic research with cross sectional design. The sampling technique is proportional sampling with a sample size of 170 people. analysis found a history of diseases that are highly associated with the implementation of Antenatal care and Birt Attendant selection at Lhoksuon Health Center in North Aceh District with p< 0.05 obtained by PR of 1048 dengan 95% CI 62,128-3176 means history of disease 1048 times has a relationship with the implementation of antenatal care and the selection of labor in the working area of ​​Lhoksukon Community Health Center in North Aceh in 2020. It is hoped that pregnant women can increase their knowledge of pregnancy and childbirth so that the mother is ready to undergo pregnancy and childbirth process safely and safely. B S T R A K AKI merupakan salah satu target pembangunan dan salah satu indikator yang peka dalam menggambarkan kesejahteraan masyarakat di suatu Negara. Dalam hal ini upaya untuk menurunkan AKI ini sangat membutuhkan pelayanan Ante Natal Care (ANC) dan Intranatal Care (INC) yang berkualitas. Tujuan dalam penelitian ini adalah untuk menganalisis faktor yang berhubungan dengan pelaksanaan Antenatal care dan pemilihan persalinan di Puskesmas Lhokdukon Kabupaten Aceh Utara. Populasi dalam penelitian ini yaitu ibu hamil trimester tiga. Teknik pengambilan sampel secara proporsional sampling dengan jumlah sampel 170 orang. Hasil penelitian ini didapati nilai p > 0,05 diperoleh PR sebesar 1048 dengan 95% CI 62,128-3176 berarti riwayat penyakit 1048 kali memiliki hubungan dengan pelaksanaan antenatal care dan pemilihan persalinan di wilayah kerja puskesmas Puskesmas Lhokdukon Kabupaten Aceh Utara tahun 2020. Diharapkan bagi ibu hamil agar dapat meningkatkan lagi pengetahuan tentang kehamilan dan proses persalinan sehingga ibu siap dalam menjalani kehamilan dan proses persalinan dengan sehat dan selamat.